Developing a proteomic approach through structural characterization of bacteriophage K - Onder, Behlis; Erdogdu, Berna; Onder, Sefik; Ozbek, Tulin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2026)
The global rise of antimicrobial resistance has renewed interest in phage therapy as a viable alternative to conventional antibiotics. Reliable assessment of the therapeutic potential of bacteriophages requires advanced analytical strategies to elucidate their structural attributes, heterogeneity, and purity profiles. In this study, the lytic Staphylococcus phage K-active against antibiotic-resistant Staphylococcus aureus strains-was selected as a model for comprehensive analytical characterization. Capillary isoelectric focusing (cIEF) was first employed to reveal charge heterogeneity of the phage proteins and distinguish empty from genome-filled capsid particles. Subsequently, a newly developed weak anion exchange chromatography (WAX) method was then applied to separate capsid variants according to retention times. Peptide mapping using LC-QTOF-MS-based proteomics enabled confident identification of 11 structural and functional proteins, including the major capsid, portal, tail sheath, muralytic enzyme, DNA polymerase, and receptor-binding proteins (RBPs). In addition, post-translational modifications (PTMs) such as phosphorylation, acetylation, deamidation, oxidation, and glycosylation were detected, and these changes were evaluated for their potential impact on protein structure, function, and stability. Collectively, these findings highlight the precision and reliability of advanced analytical platforms and underscore their utility both for the characterization of newly isolated or existing phages and for the development of novel phage-based biotechnological strategies.
Keywords: Bacteriophage K; Staphylococcus aureus; Capillary isoelectric focusing; Weak anion exchange chromatography; Peptide mapping; PROTEIN; PHOSPHORYLATION; PALMITOYLATION; IDENTIFICATION; GLYCOSYLATION; CONTRIBUTES; PEPTIDE; SITE; Biochemistry & Molecular Biology; Chemistry